A taxonomic account of Utricularia Linn. from Bangladesh - Rahman, M Oliur (Bangladesh Journal of Plant Taxonomy, 2005)
A taxonomic account of eight species of Utricularia Linn. viz. U. aurea Lour., U. bifida Lin., U. caerulea Linn., U. gibba Linn., U. inflexa Forsk., U. minutissima Vahl, U. scandens Benj. and U. stellaris L. f. has been provided from Bangladesh. An updated nomenclature including important synonyms, habitat and distribution have been furnished under each species. A key has also been given for easy identification of the species. Key words Utricularia, taxonomy, Bangladesh DOI: 10.3329/bjpt.v12i2.603 Bangladesh J. Plant Taxon. 12(2): 63-70, 2005 (December)